2021
DOI: 10.1002/1348-9585.12303
|View full text |Cite
|
Sign up to set email alerts
|

Is locomotion training effective for middle-aged workers?

Abstract: Objectives Locomotion training (LT) consisting of single‐leg standing and squatting was developed to help prevent locomotive syndrome (LS), and is typically used in older people. The objective of this study was to examine the effects of LT on young and middle‐aged people. Methods This study was performed at two companies. Workers in company A engaged in LT five times/week for 1 year, whereas workers in company B did not. Baseline and follow‐up checkups consisted of ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…Notably, our study found a median GLFS-25 of 6 at baseline, whereas a previous study 23) found a median value of 10 at baseline. Another study found that locomotion training improved the GLFS-25 among middle-aged workers (mean age: 46.0 years) 24) . To improve the GLFS-25, locomotion training should be initiated at a younger age and among those with the lowest possible GLFS-25 scores.…”
Section: Discussionmentioning
confidence: 96%
“…Notably, our study found a median GLFS-25 of 6 at baseline, whereas a previous study 23) found a median value of 10 at baseline. Another study found that locomotion training improved the GLFS-25 among middle-aged workers (mean age: 46.0 years) 24) . To improve the GLFS-25, locomotion training should be initiated at a younger age and among those with the lowest possible GLFS-25 scores.…”
Section: Discussionmentioning
confidence: 96%
“…The purpose of LS examinations in our working-age population was to prevent occupational accidents such as falls at work. Nishimura et al stated that to prevent LS, it is necessary to develop exercise habits early and create an environment where the working-age population can exercise at work [ 40 ]. A decrease in the number of remaining teeth was associated with difficulty in standing movements in the present study, which suggests that oral frailty prevention measures should be used to prevent LS in the working-age population.…”
Section: Discussionmentioning
confidence: 99%